Alfalfa Root Growth Rate Correlates with Progression of Microtubules during Mitosis and Cytokinesis as Revealed by Environmental Light-Sheet Microscopy - Vyplelová, Petra; Ovečka, Miroslav; Šamaj, Jozef (Frontiers in Plant Science, 2017)
Cell division and expansion are two fundamental biological processes supporting indeterminate root growth and development of plants. Quantitative evaluations of cell divisions related to root growth analyses have been performed in several model crop and non-crop plant species, but not in important legume plant Medicago sativa. Light-sheet fluorescence microscopy (LSFM) is an advanced imaging technique widely used in animal developmental biology, providing efficient fast optical sectioning under physiological conditions with considerably reduced phototoxicity and photobleaching. Long-term 4D imaging of living plants offers advantages for developmental cell biology not available in other microscopy approaches. Recently, LSFM was implemented in plant developmental biology studies, however, it is largely restricted to the model plant Arabidopsis thaliana. Cellular and subcellular events in crop species and robust plant samples have not been studied by this method yet. Therefore we performed LSFM long-term live imaging of growing root tips of transgenic alfalfa plants expressing the fluorescent molecular marker for the microtubule-binding domain (GFP-MBD), in order to study dynamic patterns of microtubule arrays during mitotic cell division. Quantitative evaluations of cell division progress in the two root tissues (epidermis and cortex) clearly indicate that root growth rate is correlated with duration of cell division in alfalfa roots. Our results favour non-invasive environmental LSFM as one of the most suitable methods for qualitative and quantitative cellular and developmental imaging of living transgenic legume crops.